Prenatal nicotine exposure and development of nicotinic and fast amino acid-mediated neurotransmission in the control of breathing - Fregosi, Ralph F. (2008)
There is mounting evidence that neonatal animals exposed to nicotine in the prenatal period exhibit a variety of anatomic and functional abnormalities that adversely affect their respiratory and cardiovascular control systems, but how nicotine causes these developmental alterations is unknown. The principle that guides our work is that PNE impairs the ability of nicotinic acetylcholine receptors (nAChRs) to modulate the pre-synaptic release of both inhibitory (particularly GABA) and excitatory (glutamate) neurotransmitters, leading to marked alterations in the density and/or function of receptors on the (post-synaptic) membrane of respiratory neurons. Such changes could lead to impaired ventilatory responses to sensory afferent stimulation, and altered breathing patterns, including central apneic events. In this brief review we summarize the work that lead to the development of this hypothesis, and introduce some new data that support and extend it.